Photocatalytic degradation of oily wastewater : effect of catalyst concentration load, irradiation time and temperature - Norlaila, Mok (2009)
The photocatalytic degradation of an oily wastewater over titanium dioxide, TiO2 suspensions was investigated. The study focused on the effects of various operating parameters on the treatment efficiency which include catalyst concentration load, irradiation time and reaction temperature. Catalyst concentration load was studied in the range 0.5-2.5 g/L, irradiation time between 0-150 min and the reaction temperature in the range 30-60 oC. The regression and graphical analysis with statistical significance for this researched were done using Design Expert 7 software. In order to visualize the relationship between the experimental variables and responses, the response surface was generated from the model. Treatment efficiency, which was expressed in terms of chemical oxygen demand (COD), generally increased with decreasing initial COD. Higher treatment efficiency involved the increasing of irradiation time with temperature. The percent of degradation nearly achieved 51% depending on the conditions employed. The optimum conditions for this research work can be acquired at catalyst concentration of 0.5 g/L while the effect of temperature and reaction time were conducted at 60 oC and 150 min respectively.